DETERMINAN MINAT GENERASI Z MEMBELI SUKUK RITEL DENGAN MEDIA SOSIAL SEBAGAI VARIABEL MODERATING - Nurul Izzah; Andri Soemitra; Zuhrinal M Nawawi (Mumtaz: Jurnal Ekonomi dan Bisnis Islam, 2023)
The purpose of this study is to examine the determinants of Generation Z's interest in buying retail Sukuk with social media as a moderating variable. This paper uses data obtained from a structured questionnaire. Then test the hypotheses developed to answer research questions. The survey was conducted on 260 Generation Z samples in Padangsidimpuan City and analyzed using SEM-PLS. The results showed that yield, financial literacy, and social media significantly affected the purchase intention of Generation Z retail Sukuk. However, social media did not significantly moderate the relationship between return, financial risk, and financial literacy in increasing interest in buying retail Sukuk. buy retail bonds. buy retail bonds. Generation Z Sukuk. To increase Generation Z's interest in buying retail Sukuk, financial sector authorities need to improve education and outreach regarding retail Sukuk through social media platforms. As far as the authors know, there has been no research that focuses explicitly on social media in moderating the variables that influence the purchase intention of Generation Z Retail Sukuk. Keywords: Retail Sukuk, Interest, Social Media, Moderation